2012
DOI: 10.1016/j.bbadis.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in cervical cancer: Chemopreventive and chemotherapeutic effects of polyphenols

Abstract: Cervical cancer lesions are a major threat to the health of women, representing the second most common cancer worldwide. The unanimously recognized etiological factor in the causation of cervical cancer is the infection with human papilloma virus (HPV). HPV infection, although necessary, is not per se sufficient to induce cancer. Other factors have to be involved in the progression of infected cells to the full neoplastic phenotype. Oxidative stress represents an interesting and under-explored candidate as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 148 publications
2
101
0
5
Order By: Relevance
“…In recent times, there has been renewed interest in natural products research, mostly motivated by the lower prevalence of undesired side effects of these compounds [23,44,94]. -azinobis-(3-ethylbenzthiazoline-6-sulfonic acid); DPPH: 1,1-Diphenyl-2-picrylhydrazyl.…”
Section: Rational Design Of Antioxidants; Struc-ture-activity Relatiomentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, there has been renewed interest in natural products research, mostly motivated by the lower prevalence of undesired side effects of these compounds [23,44,94]. -azinobis-(3-ethylbenzthiazoline-6-sulfonic acid); DPPH: 1,1-Diphenyl-2-picrylhydrazyl.…”
Section: Rational Design Of Antioxidants; Struc-ture-activity Relatiomentioning
confidence: 99%
“…HCAs and their derivatives have a broad spectrum of biological activities including antitumoral [42][43][44][45], antimicrobial [46], antioxidant [47][48][49][50][51][52] and neuroprotective effects [53][54][55].…”
Section: Coo Hmentioning
confidence: 99%
“…Among the compounds studied, the antioxidant and chemopreventive activity of ellagic acid and Annona muricata have been demonstrated (12)(13)(14)(15)(16)(17)25). It has been demonstrated by in vitro models that both compounds induce cell cycle arrest in the G1 phase, DNA repair and apoptosis (22,25).…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies investigating the role of diet and nutritional status in cervical HPV have suggested that certain natural compounds provide a protective effect against cervical dysplasia and HPV persistence (8,14,15,20,23). Among the compounds studied, the antioxidant and chemopreventive activity of ellagic acid and Annona muricata have been demonstrated (12)(13)(14)(15)(16)(17)25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation